2011
DOI: 10.1249/mss.0b013e3181ed0ea3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Training on Airway Inflammation in Asthmatic Patients

Abstract: aerobic training reduces sputum eosinophil and FeNO in patients with moderate or severe asthma, and these benefits were more significant in subjects with higher levels of inflammation. These results suggest that aerobic training might be useful as an adjuvant therapy in asthmatic patients under optimized medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
187
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(214 citation statements)
references
References 24 publications
13
187
0
14
Order By: Relevance
“…More recently, an excellent study from Mendes et al demonstrated for the first time that 12 weeks of moderate intensity aerobic exercise in moderate and severe asthmatic patients resulted in decreased number of eosinophils in induced sputum, proving the concept that aerobic exercise presents anti-inflammatory effects for asthma [14].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, an excellent study from Mendes et al demonstrated for the first time that 12 weeks of moderate intensity aerobic exercise in moderate and severe asthmatic patients resulted in decreased number of eosinophils in induced sputum, proving the concept that aerobic exercise presents anti-inflammatory effects for asthma [14].…”
mentioning
confidence: 99%
“…This gradual change of concept represent a big advance against old paradigms, and is based in a growing number of clinical and experimental studies showing that the regular practice of aerobic exercises in appropriate volume and intensity results in several physical and psychological beneficial effects to asthmatic patients [5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As evidências na literatura têm demonstrado que os exercícios aeróbios podem proporcionar aos pacientes: melhora dos fatores relacionados à qualidade de vida 34,24,35 e do controle clínico 36 , bem como redução do número de crises e uso da medicação de alívio 37,24,35 , do broncoespasmo induzido pelo exercício 34 , da hiperresponsividade das vias aéreas 38 , do uso de corticosteróide 34 , do risco de exacerbação da asma 27,24,39 . Atualmente, tem-se sugerido que o exercício físico tenha um efeito antiinflamatório na asma evidenciado pela redução da fração de óxido nítrico exalado (FeNO) 39,40 e redução na porcentagem de eosinófilos no escarro 39 . Apesar desses estudos, os únicos benefícios amplamente reconhecidos do treinamento físico aeróbio em pacientes asmáticos, avaliados por análise sistemática, são o aumento da capacidade aeróbica, melhora dos fatores de saúde relacionados a qualidade de vida e redução da dispneia durante o exercício 22 .…”
Section: Exercício Aeróbio X Asmaunclassified